Malaysian labour law: equalizing the differences between part time employee and full time employee status and rights / Noor Nadiah Zainol Abidin...[et al.] - Zainol Abidin, Noor Nadiah; Mohd Rosni, Nur Khairunnisa; Razali, Ras Emil Suraya (Faculty of Law, 2013)
The study is carried out to assess the effectiveness of the Employment (Part-Time Employees) Regulations 2010 in protecting the rights of the part-time employees in Malaysia and their status in comparison with the full time employees. This research is a qualitative type of research where the focus is on the data gathered from various written sources and also from the interviews conducted with the legal experts. This research paper will particularly focus on the rate of overtime payment entitled for the part-time employees and their rights over EPF and SOCSO. The provisions provided under the regulation are very limited and inadequate in protecting the rights of part-time employees. There are rights which the part-time employees are entitled to but are not covered in the regulation such as EPF and SOCSO where the confusion regarding their rights then arises. The research will then focus on the position of the part-time employees in Malaysia in context of overtime payment and rights to EPF and SOCSO and the effect of "part-time" status over their rights. The research concludes that the regulation did not sufficiently protect the part-time employees. Therefore, some recommendations have been proposed at the end of the research to improve the regulation in order to ensure that the part-time employees in Malaysia are well protected.